2018
DOI: 10.1016/j.athoracsur.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Lung Volume Reduction Surgery in Patients With Severely Impaired Diffusion Capacity

Abstract: Selected patients with severely impaired Dlco of less than 20% can cautiously be considered as potential candidates if hyperinflation is severe and the lungs show areas with advanced destruction as targets for resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
2
17
0
1
Order By: Relevance
“…However, in heterogeneous emphysema, the resected tissue is functionless und will not further impair gas exchange, but the patient should profit from the effect of correcting hyperinflation. Recently published by our group (13) and already reported by Ciccone and Cooper in 2003 (5), patients with a diffusion capacity below 20% predicted were operated with zero mortality and a good profit. The 33 patients from Zurich showed preoperative pulmonary function values (FEV1, TLC, RV, RV/TLC) within the usual range for LVRS but had a severely impaired diffusion capacity (median 15%, interquartile range [13][14][15][16][17][18].…”
Section: Impaired Diffusion Capacitymentioning
confidence: 76%
See 2 more Smart Citations
“…However, in heterogeneous emphysema, the resected tissue is functionless und will not further impair gas exchange, but the patient should profit from the effect of correcting hyperinflation. Recently published by our group (13) and already reported by Ciccone and Cooper in 2003 (5), patients with a diffusion capacity below 20% predicted were operated with zero mortality and a good profit. The 33 patients from Zurich showed preoperative pulmonary function values (FEV1, TLC, RV, RV/TLC) within the usual range for LVRS but had a severely impaired diffusion capacity (median 15%, interquartile range [13][14][15][16][17][18].…”
Section: Impaired Diffusion Capacitymentioning
confidence: 76%
“…Recently published by our group (13) and already reported by Ciccone and Cooper in 2003 (5), patients with a diffusion capacity below 20% predicted were operated with zero mortality and a good profit. The 33 patients from Zurich showed preoperative pulmonary function values (FEV1, TLC, RV, RV/TLC) within the usual range for LVRS but had a severely impaired diffusion capacity (median 15%, interquartile range [13][14][15][16][17][18]. Their lung function significantly improved three months after surgery (FEV1% predicted by 26%) and even the DLCO significantly increased by 60% and remained higher than pre-operative for the subsequent year (FEV1% predicted still 21% higher and DLCO 27 % higher compared to preoperatively).…”
Section: Impaired Diffusion Capacitymentioning
confidence: 76%
See 1 more Smart Citation
“…A recent paper by Caviezel et al [2018] demonstrated that DLCO actually significantly improves post-LVRS in patients with a pre-operative DLCO less than 20%, strengthening the argument that resection of non-contributing parenchyma…”
mentioning
confidence: 86%
“…Hyperinflation is also radiologically evaluated using signs such as flattened diaphragm and funnel chest. FEV 1 and diffusion capacity values below 20% predicted are only accepted in cases of heterogeneous emphysema [13] where the target area of resection is (as suggested from perfusion scan and CT scan) obviously functionless lung tissue. Concerning homogeneous emphysema, patients with severe hyperinflation and a D LCO >20% predicted are also considered as possible surgical candidates.…”
Section: Inclusion Criteria For Lvrsmentioning
confidence: 99%